2008
DOI: 10.1074/jbc.m709080200
|View full text |Cite
|
Sign up to set email alerts
|

Antihemostatic Activity of Human Granzyme B Mediated by Cleavage of von Willebrand Factor

Abstract: The cytotoxic lymphocyte protease granzyme B (GrB) is elevated in the plasma of individuals with diseases that elicit a cytotoxic lymphocyte-mediated immune response. Given the recently recognized ability of GrB to cleave extracellular matrix proteins, we examined the effect of GrB on the pro-hemostatic molecule von Willebrand factor (VWF). GrB delays ristocetininduced platelet aggregation and inhibits platelet adhesion and spreading on immobilized VWF under static conditions. It efficiently cleaves VWF at two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
47
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 64 publications
6
47
1
Order By: Relevance
“…Other substrates have included proteins involved in blood clotting, and angiogenesis. 94,97 Additionally, GrB cleaves a number of cell receptors, which may influence their ability to respond to growth and survival signals, as well as promote the production of autoantigens. 98,99 Several studies have suggested an inflammatory role for GrA.…”
Section: Additional Roles Of Grsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other substrates have included proteins involved in blood clotting, and angiogenesis. 94,97 Additionally, GrB cleaves a number of cell receptors, which may influence their ability to respond to growth and survival signals, as well as promote the production of autoantigens. 98,99 Several studies have suggested an inflammatory role for GrA.…”
Section: Additional Roles Of Grsmentioning
confidence: 99%
“…In support of this theory, reports have demonstrated GrB-mediated proteolysis of extracellular matrix proteins. [94][95][96] A consequence of this may be perforinindependent cell death of adherent cells, via anoikis, where adherent cells die following detachment from the extracellular matrix. Alternatively, cleavage of these proteins may also influence cellular adhesion and migration processes.…”
Section: Additional Roles Of Grsmentioning
confidence: 99%
“…Although SERPINB9 is an efficient inhibitor of gzmB inside the cell, gzmB is also known to be present and active extracellularly, where it is likely to be involved in the degradation of extracellular matrix molecules, [62][63][64][65][66][67] and may have pathophysiological functions in blood coagulation 63 and atheromatous disease (reviewed by Chamberlain and Granville 68 and elsewhere in this volume). Past investigations into potential extracellular inhibitors of gzmB have suggested a2-macroglobulin or SERPINA1 as possible candidates; 69 however, SERPINA1 shows no gzmB inhibitory activity in vitro.…”
Section: Regulation Of Extracellular Gzmbmentioning
confidence: 99%
“…Cleavage of the prohemostatic molecule, von Willebrand factor, by GrB was shown to delay platelet aggregation, suggesting that GrB may have antithrombotic properties. 62 In vitro experiments have also shown the ability of GrB to cleave several components of the ECM including fibronectin, vitronectin, laminin, and fibrillin-1, suggesting a causative role for GrB in inducing cell detachment and promoting further damage to the ECM. 35,58,60,61 In particular, GrB cleavage of aggrecan, a cartilage proteoglycan degraded in RA, has led to several studies investigating the pathological role of GrB in this disease.…”
Section: Extracellular Granzymes In Chronic Inflammationmentioning
confidence: 99%
“…Human VWF coated on plate was cleaved by 50 and 100 nM recombinant human GrB after 1 h. GrB cleavage has similar efficiency to ADAMTS-13 cleavage of VWF. Human fibrinogen coated on plate was cleaved by 10-100 nM recombinant human GrB after 1 h. 62 Extracellular roles for GrH, K, and M remain unknown at present. Although the possibility remains that these granzymes are exclusively intracellular, under certain conditions they also accumulate in the extracellular milieu.…”
Section: Fibrillin-1mentioning
confidence: 99%